ECOLOGICAL ROLES OF MERCURY ACCUMULATION IN MANGROVE FORESTS OF SEKOTONG, WEST NUSA TENGGARA, INDONESIA - Anis Syakiratur Rizki; Dining Aidil Candri; Mursal Ghazali (BIOTROPIA, 2026)
ARTICLE HIGLIGHTS- Examines mercury accumulation in leaves and roots of nine mangrove species near gold mines- Shows mangroves can stabilize, extract, and accumulate mercury- Evaluates translocation, bioaccumulation, and phytoremediation potential- Identifies mangroves as indicators of mercury contamination- Supports selecting suitable mangrove species for reforestation of contaminated coastsABSTRACTThis study aims to determine the ability to analyze the accumulation of mercury heavy metals in mangrove organs (leaves and roots) and sediments in potentially polluted areas of the coastal mangrove ecosystem of Sekotong, West Lombok Regency, West Nusa Tenggara, Indonesia. This research was conducted on mangrove ecosystems adjacent to conventional gold processing areas. Mercury content analysis was carried out on nine types of mangroves found (Avicennia marina, Bruguiera cylindrica, Clerodendrom inerme, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Scyphiphora hydrophyllaceae, Bruguiera gymnorrhiza, and Lumnitzera racemosa) including leaves, mangrove roots and sediments found under the stands of each type. Sample testing using the AAS (Atomic Absorbtion Spectrophotometer) method. The results showed that the content of mercury heavy metals in the lower substrate of each type of mangrove showed an average of 0.30±0.122 ppm, which was on average lower than the average accumulation of mercury in leaves (0.48±0.716 ppm) and roots (0.33±0.204 ppm). Further analysis showed that four mangroves had the ability to phytostabilize against mercury heavy metals with an average value of TSFs of more than one (Bruguiera gymnorrihza, Clerodendrom inerma, Lumnitzera racemosa, Scyphiphora hydrophyllacea), and five others as phytoextractors (Avicennia marina, Bruguiera cylindrica, Rhizophora mucronata, Rhizophora apiculata, and Rhizophora stylosa) with the value of TSFs>1. The interval of leaf BAFs was between 0.02-15.73 with an average of 2.65±4.961 leaf BAFs and root BAFs between 0.04-4.33 with an average of 1.45±1.280 while the FTD value of Sekotong mangrove leaves at the interval (-0.48)-8.12 with an average of 1.10±2.275 and the root FTD at the interval (-5.55)-3.87 with an average of -0.10±2.449. Root FTD values showing a negative mean value (-0.10±2.449) indicate that the distribution of mercury tends to be higher in the upper part of the plant (leaves).